The Evolution of Gender Quota Research on Corporate Boards: A Thematic Literature Review - Kavalieraki-Foka, Dimitra; Asonitou, Sofia; Tourna, Eleni; Krambia-Kapardis, Maria; Kottara, Chara (My University, 2025)
The initial law mandating a gender balance on corporate committees was passed in Norway at the dawn of the 21st century, and since then, the subject of gender quotas has attracted increasing attention from researchers. There should be a temporal mapping of research to identify changing scientific priorities and emerging directions. The goal of this literature study is to do more than just count and organise research or make statistical conclusions; it aims to show how the scientific discussion on this topic has developed over time and to present the literature as an active and ongoing conversation. Combining a concept-centric approach for spotting trends and themes, using as a basis the content of the analysed research, with the SALSA framework as a methodological tool for conducting this literature review, delivered results. From early structural and compliance-based studies to more recent, sophisticated investigations of how gender quotas interact with power dynamics, organisational culture, and sustainable corporate transformation, the review notes a clear change in the literature. Reflecting a larger and more critical awareness of gender diversity in government, the emphasis has changed over time from legal enforcement and representation toward emerging themes including ESG performance, ethical leadership, innovation, intersectionality, and symbolic inclusion. The results repeatedly highlight that in this changing terrain, the favourable contribution of gender-diverse boards is improving non-financial reporting, generating better financial results, and advancing more inclusive, transparent, and responsible corporate practices. This work highlights understudied areas, traces the development of important themes and changes in scientific priorities over time, and provides direction for the next studies.
Keywords: Concept-centric approach; Gender diversity; Thematic evolution; Corporate boards; SALSA framework; Gender quotas